DIGITAL LITERACY COMPETENCE OF MOVER TEACHERS IN IMPLEMENTING THE INDEPENDENT CURRICULUM IN SUMBAWA BESAR CITY - Soepriyanti, Henny; Waluyo, Untung; Fitriana, Eka; Riyanto, Andra Ade (Esteem Journal of English Education Study Programme, 2025)
This study examines the efforts of Mover Teachers in Sumbawa Besar City to implement digital literacy principles in line with the Independent Curriculum. Using a multi-case study approach, it reveals that while teachers are adept at using basic digital tools like Zoom and Google Classroom, they struggle with integrating more advanced platforms like Google Docs and data analytics tools. Continuous Professional Development (CPD) and peer collaboration are key enablers, with training workshops fostering innovative teaching practices. However, challenges such as inadequate infrastructure, limited internet access, and inconsistent high-level training hinder broader adoption. Teachers also face difficulties managing digital classrooms and developing students' critical assessment skills, highlighting the need for targeted professional development. Grounded in Vygotsky's sociocultural theory and Bandura's social learning theory, the study emphasizes the importance of scaffolding and collaborative learning to enhance digital competencies. Addressing these barriers is essential for equitable and effective curriculum implementation, equipping educators and students with 21st-century skills for a digitally connected world.